Sintering induced impurity phase in La1.8-Sr0.2-CuO 4-d - Serafini, D.; Caneiro, Alberto; Abriata, José Pablo (Comisión Nacional de Energía Atómica; Argentina)
Fil: Serafini, D. Comisión Nacional de Energía Atómica; Argentina